PANCASILA AND NATIONAL RESILIENCE IN THE ERA OF GLOBALIZATION: SOCIAL AND EDUCATIONAL PERSPECTIVES - Gan Gan Nurbanani Yusuf; Isnan Chodri (JUNAGARA: Jurnal Ilmiah Hukum dan Kenegaraan, 2025)
This study aims to analyze the implementation of Pancasila values and their contribution to strengthening the social and ideological resilience of students at MTs Al-Manar Tengaran, Semarang Regency, in the era of globalization. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, questionnaires, and document analysis involving the principal, teachers, and students. The findings reveal that Pancasila values have been integrated into classroom learning processes, school culture, and co-curricular as well as extracurricular activities. The data indicate that 84% of students demonstrate strong tolerance attitudes, 88% actively participate in mutual cooperation activities, and 85% express pride in national symbols and identity. These findings suggest a positive contribution to strengthening students’ social and ideological resilience. However, students’ critical digital literacy skills require further improvement, as only 54% reported being able to independently evaluate information accuracy. The study concludes that while the implementation of Pancasila values has established a solid foundation for social and ideological resilience, reinforcement in digital literacy and critical thinking-based learning is necessary to respond effectively to the challenges of globalization.